All Days 2012
DOI: 10.2118/157109-ms
|View full text |Cite
|
Sign up to set email alerts
|

Triazine-Based Scavengers: Can They Be a Potential for Formation Damage

Abstract: Hydrogen sulfide (H 2 S) scavengers have been used extensively in different field operations such as drilling and acid stimulation treatments. Typically, H 2 S scavengers are preliminarily designed to react effectively at different in-situ conditions. For example, Triazine-based scavengers are designed for neutral-high pH conditions, while aldehyde-based scavengers are intended for low pH conditions. However, reaction products of these scavengers with H 2 S could lead to potential formation damage.The efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…One prominent misconception is that this solid fouling deposit is the so-called “over-spent” condition of triazines which results in the formation of 1,3,5-trithiane (structure IV, as shown in Figure ). There are many earlier studies that incorrectly assign this species as a reaction product. ,,,, In fact, as this review will show, the reaction of all triazines terminates at dithiazine (the second sulfur molecule substitution), and 1,3,5-trithiane (IV) is not formed in any significant quantity. It is therefore the dithiazine which causes the observed deposits/fouling.…”
Section: Reaction Of Triazines and H2s: Critical Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…One prominent misconception is that this solid fouling deposit is the so-called “over-spent” condition of triazines which results in the formation of 1,3,5-trithiane (structure IV, as shown in Figure ). There are many earlier studies that incorrectly assign this species as a reaction product. ,,,, In fact, as this review will show, the reaction of all triazines terminates at dithiazine (the second sulfur molecule substitution), and 1,3,5-trithiane (IV) is not formed in any significant quantity. It is therefore the dithiazine which causes the observed deposits/fouling.…”
Section: Reaction Of Triazines and H2s: Critical Reviewmentioning
confidence: 90%
“…There are many earlier studies that incorrectly assign this species as a reaction product. 13,16,17,27,28 In fact, as this review will show, the reaction of all triazines terminates at dithiazine (the second sulfur molecule substitution), and 1,3,5-trithiane (IV) is not formed in any significant quantity. It is therefore the dithiazine which causes the observed deposits/fouling.…”
Section: Triazine Chemistry Introduction and Commonmentioning
confidence: 94%
See 1 more Smart Citation
“…It was also found that long exposure time between triazine-based scavengers and H 2 S can result in significant scavenging efficiency even at low pH values. In recent years triazine-based scavengers have been extensively used in stimulation treatments to remove H 2 S from flowed back fluids [8]. Triazine derivatives were also applied as pesticides.…”
Section: Biocidal Products and Microbial Control For Hydrocarbon Reservoirmentioning
confidence: 99%
“…The resulting product is the cyclic trimer of thioformaldehyde or 1,3,5-trithiane (structure 2 of Figure ). In fact, 1,3,5-trithiane is often mistakenly thought to be the ultimate reaction product from MEA triazine over-reacted with H 2 S. In fact, the ultimate byproduct in this reaction mechanism is amorphous polymeric dithiazine, a polymer from the 2-sulfur species, dithiazine. , …”
Section: Introductionmentioning
confidence: 99%